How universities promote economic growth - Yusuf, Shahid, 1949-; Nabeshima, Kaoru (Washington, D.C. : World Bank, 2007)
With the competitiveness of firms in an open and integrated world environment increasingly reliant on technological capability, universities are being asked to take on a growing role in stimulating economic growth. Beyond imparting education, they are now viewed as sources of industrially valuable technical skills, innovations, and entrepreneurship. Developed and developing countries alike have made it a priority to realize this potential of universities to spur growth, a strategy that calls for coordinated policy actions.
University-industry links : policy dimensions / Pt.1. UIL-related policies of national governments -- Notes on UIL-related policies of national governments / University-industry knowledge transfer in Switzerland / University-industry links and U.K. science and innovation policy / Universities and public research institutions as drivers of economic development in Asia / UIL-related policies of national governments : a synthetic view / Pt.2. UIL-related policies of subnational governments -- The role of higher education and new forms of governance in economic development : the Ontario case / University-industry links in the Japanese context : between policies and practice / University-industry links : regional policies and initiatives in the United Kingdom / University-industry research collaboration and technology transfer in the United States since 1980 / Pt.3. UIL-related policies of universities -- Building research universities for knowledge transfer : the case of China / Approaches to university-industry links : the case of the National University of Singapore / University-industry links and enterprise creation in India : some strategic and policy issues / The entrepreneurial university : the idea and its critics / Pt.4. Corporate strategies of multinational corporations and small and medium enterprises -- Beyond absorptive capacity : the management of technology for a proactive corporate strategy toward university-industry links / Corporate strategies in university-industry links in France / Specific approaches to university-industry links of selected companies in Thailand and their relative effectiveness
Includes bibliographical references and index.
Keywords: Academic-industrial collaboration -- Economic aspects; Business and education; Universities and colleges -- Economic aspects; Education, Higher -- Economic aspects